2014
DOI: 10.1016/j.ultsonch.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and sonocatalytic property of rod-shape Sr(OH)2·8H2O

Abstract: A novel rod-shape sonocatalyst Sr(OH)2·8H2O was prepared by a facile precipitation method, and characterized by X-ray powder diffraction, transmission electron microscopy, Fourier transform infrared spectroscopy and UV-vis absorption spectroscopy. Comparative sonocatalytic degradation experiments were carried out in different conditions under ultrasonic irradiation by using rhodamine B (RhB) as the model substrate, indicating that Sr(OH)2·8H2O was highly sonocatalytic. Total organic carbon experiment demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Notably, mixed phases of SrCO 3 and hydrated strontium hydroxides (Sr(OH) 2 •xH 2 O, where x is the number of molar coefficient of water in strontium hydroxide solid) were obtained from all other synthesis conditions (results shown in Supplementary Materials: Figures S1 and S2). Typical diffraction peaks correspond well with (110), (111), (021), (002), (012), (130), (220), (221), (132) and (113) orthorhombic SrCO 3 lattice planes [34,36], whereas other diffraction peaks match with those of previously reported Sr(OH) 2 •H 2 O [37] and Sr(OH) 2 •8H 2 O phases [38]. The formation of Sr(OH) 2 xH 2 O is possibly due to adsorbed alcohol, promoting the addition of OH functional groups on the solid surface [39], upon solvothermal crystallization of Sr-containing products.…”
Section: Effects Of Synthesis Conditionssupporting
confidence: 86%
“…Notably, mixed phases of SrCO 3 and hydrated strontium hydroxides (Sr(OH) 2 •xH 2 O, where x is the number of molar coefficient of water in strontium hydroxide solid) were obtained from all other synthesis conditions (results shown in Supplementary Materials: Figures S1 and S2). Typical diffraction peaks correspond well with (110), (111), (021), (002), (012), (130), (220), (221), (132) and (113) orthorhombic SrCO 3 lattice planes [34,36], whereas other diffraction peaks match with those of previously reported Sr(OH) 2 •H 2 O [37] and Sr(OH) 2 •8H 2 O phases [38]. The formation of Sr(OH) 2 xH 2 O is possibly due to adsorbed alcohol, promoting the addition of OH functional groups on the solid surface [39], upon solvothermal crystallization of Sr-containing products.…”
Section: Effects Of Synthesis Conditionssupporting
confidence: 86%
“…Lopez-Sanchez et al have concluded PVA-stabilized gold NPs may have its activity affected by the stabilizer for CO oxidation reactions. They proposed an efficient water extraction method that is able to clean the NPs surface, maintaining their size and morphology [30]. The Au/calc-Sr sup catalyst is very active considering that no base was added to the reaction medium; therefore, we performed an extraction with acetone, and it was applied to this material with some modifications.…”
Section: Resultsmentioning
confidence: 99%
“…The supports were prepared according to literature with modifications [30]. For one of them, 50 mL of strontium nitrate (1 mol L −1 ) and 50 mL of sodium hydroxide (2 mol L −1 ) were mixed and constantly stirred for 1 h. The mixture was centrifuged for 5 min at 2400 rpm and a white precipitate was obtained by pouring the supernatant off.…”
Section: Catalytic Supports Preparationmentioning
confidence: 99%
“…In the search to find a cheap and straight route to obtain the SrCO 3 phase, it was chose to dry Sr(OH) 2 at ambient atmosphere to take advantage of the reaction with CO 2 present in the air [42,43,44,45,46,47]. …”
Section: Resultsmentioning
confidence: 99%
“…Taking into account some reports about SrCO 3 -Sr(OH) 2 composite as background [42,43,44,45,46,47], and due the SrCO 3 -Sr(OH) 2 /PPy nanocomposite has not been studied as a photocatalyst candidate, this manuscript describes a modified strategy for the preparation of SrCO 3 -Sr(OH) 2 nanocomposite, followed by coating with the semiconducting polypyrrole (PPy) to increase its photoactivity in the visible light range. Both SrCO 3 -Sr(OH) 2 and SrCO 3 -Sr(OH) 2 /PPy nanocomposites were tested for photodegradation of MB dye under visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%